Le Nil dans les récits de voyage de la fin du Moyen Âge, entre réalité et légende - Sylvie Bazin-Tacchella; Capucine Herbert (Viatica)
Abstract: The reason why medieval travelers who visit Egypt usually devote parts of their narrative to the river Nile is that they find it a fascinating place to discover. However, their descriptions vary from observation to bookish knowledge or myths. In this article we study how the Nile is described, we also list the realia and mirabilia associated with it in the narratives of the late Middle Ages.